MANAJEMEN PENDIDIKAN ISLAM DI MDTA NURUL FALAH - Rika Rahman, Susi Sumiati, Adi Rosadi (JIP: Jurnal Ilmu Pendidikan, 2024)
This research aims to analyze and improve the quality of Islamic education management at MDTA Nurul Falah Cimanggu. The results of the research show that there are several challenges in the management of Islamic education at MDTA Nurul Falah, such as a lack of quality human resources, a lack of curriculum development that is relevant to the local context. Based on these findings, several improvement strategies are recommended, including staff training and development, revamping the curriculum with a focus on local needs. It is hoped that this research can contribute to improving the quality of Islamic education at MDTA Nurul Falah Cimanggu and also become a reference for further research in this field.